50 paintings you should know - Lowis, Kristina; Pickeral, Tamsin (Munich ; New York : Prestel, 2009)
Presents fifty paintings by major artists from the Renaissance to the twentieth century and includes a brief critical analysis of the work and a timeline for the artist.
The wanderer above the sea of fog / Caspar David Friedrich -- The raft of the medusa / Theodore Gericault -- Liberty leading the people / Eugene Delacroix -- Rain, steam and speed / William Turner -- Le Dejeuner sur l'herbe / Edouard Manet -- The artist's mother / James Abbott McNeill Whistler -- Impression-sunrise / Claude Monet -- The starry night / Vincent van Gogh -- The child's bath / Mary Cassatt -- The scream / Edvard Munch -- Mont Sainte-Victoire / Paul Cezanne -- Les demoiselles d'Avignon / Pablo Picasso -- The kiss / Gustav Klimt -- La danse / Henri Matisse -- The dream / Henri Rousseau -- Impression III (concert) / Wassily Kandinsky -- Black square / Kasimir Malevich -- Petunia No. 2 / Georgia O'Keeffe -- American gothic / Grant Wood -- The persistence of memory / Salvador Dali -- The two Fridas / Frida Kahlo -- Nighthawks / Edward Hopper -- Autumn rhythm no. 30 / Jackson Pollock -- Black on maroon / Mark Rothko -- Campbell's soup cans / Andy Warhol -- Glossary -- Index, photo credits.
Includes index.
Keywords: Painting -- Appreciation; Painters -- Biography; Pintura